Intensity of perceived stress prior to a judo tournament among male and female contestants. A preliminary study - Obminski, Z.; Mroczkowska, H. (Journal of Combat Sports and Martial Arts, 2014)
In the present research we sought to determine whether: (i) the levels precompetitive stress in male and female participants of an international judo tournament are alike, (ii) the parallel use of the questionnaire (STAI) for determination of state anxiety (SA) and visual analog scale for determination perceived stress (PS) provide results of high consistency. Material and methods. Male (n=33) and female (n=33) judo players were examined on the day of an International Judo Tournament. In the morning, few hours prior to the first struggle they were ask to fill the STAI, and to rate their current PS using the visual analog scale. The successive assessments of PS were conducted before and after warm up prior to the first struggles. Results. Precompetitive situation triggered in the morning somewhat higher SA and PS in females, but the differences were not significant. There were significant correlations between SA and PS in both sexes. Later, PS was elevating with the time to the first struggle and the difference between sexes was greater and significant. Conclusions. Female judo players responses stronger to anticipatory stress than their male counterparts, especially directly prior to the event. There are good consistency of the results regarding emotional arousal obtained from STAI and visual analog scale.